2015
DOI: 10.1128/aem.00458-15
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Colonizing Bacillus Isolates in Glucovanillin Hydrolysis during the Curing of Vanilla planifolia Andrews

Abstract: Vanilla beans were analyzed using biochemical methods, which revealed that glucovanillin disperses from the inner part to the outer part of the vanilla bean during the curing process and is simultaneously hydrolyzed by ␤-D-glucosidase. Enzymatic hydrolysis was found to occur on the surface of the vanilla beans. Transcripts of the ␤-D-glucosidase gene (bgl) of colonizing microorganisms were detected. The results directly indicate that colonizing microorganisms are involved in glucovanillin hydrolysis. Phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The microorganism involved in the curing of vanilla beans was supported by many researches ( Röling et al, 2001 ; General et al, 2009 ; Chen et al, 2015 ). In this study, Bacillus and Aspergillus were found changed during the curing process.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The microorganism involved in the curing of vanilla beans was supported by many researches ( Röling et al, 2001 ; General et al, 2009 ; Chen et al, 2015 ). In this study, Bacillus and Aspergillus were found changed during the curing process.…”
Section: Discussionmentioning
confidence: 94%
“…It was found that the structure of bacteria and fungi were closely related to the vanillin content in this study. Colonizing Bacillus isolates produced β-D-glucosidase, which mediated the glucovanillin hydrolysis and influenced the vanillin formation (Chen et al, 2015). Furthermore, it was reported that Bacillus siamensis XY18 and Bacillus subtilis XY20 isolated from vanilla beans could increase the vanillin content (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consequence is that there is no need for any initial heat treatment in hot water or in an oven, as it is performed commonly in the Indian Ocean region, in Central America or in New Guinea. During curing, many biotransformations take place due to the presence of intrinsic enzymes located in the pods and/or the action of colonizing microorganisms on the surface as evidenced by the latest findings on V. planifolia [32]. Even if the different biotransformations involved are still unclear, they will definitely contribute to the development of the final vanilla flavour that one can experience when smelling cured vanilla pods.…”
Section: The Effect Of Curing Process On Vanilla Flavourmentioning
confidence: 99%
“…We have recently found that colonizing Bacillus in vanilla beans is involved in glucovanillin hydrolysis and vanillin formation during conventional curing [14]. Therefore, we speculated that Bacillus isolates can be used to develop a new, cheap, and simple method to increase vanillin production.…”
Section: Introductionmentioning
confidence: 99%